Risk Analysis – General Approach - Danihelka, Pavel; Polednak, Pavel (Communications - Scientific letters of the University of Zilina, 2008)
The article deals with a general theory of risk analysis and corresponding risk management and provides the overview of the systematic method of risk analysis based on the MADS-MOSAR concept. Risk is represented as aflux of danger and typology of sources of danger, flux mechanism and potential targets are described. Quantification of risk is done as acombination of uncertainty and impact of an unwanted event and risk management is based on safety barriers introduction to overall process described by combination of FTA and ETA, so called “bow-tie diagram”.